Biomechanical comparison of bioresorbable F‑u‑HA/PLLA screw and tension band wire fixation in medial malleolar fractures. (2021) - SAKAI, HIROAKI; TAKADA, NAOYA; KUROYANAGI, GEN; USAMI, TAKUYA; UEKI, YOSHINO; MURAKAMI, HIDEKI
No abstract available